A brief concept of Nyegara Gunung: an intertwine of sacred mountain and mystical sea - Ida Ayu Putu Widya Indah Sari (Bali Tourism Journal, 2019)
Many legends, myths, and folktales discuss mountain and its central position for people. From base to top, the mountain summit holds the highest spiritual value, because the place is considered close to heaven. Balinese folk divided the land into three sectors: highland for the immortal beings, mainland for human, and in the dark depth trench, reside spirit of the abyss. Since the beach is the closest area to the underworld, the Balinese forefather avoided spending their time on the coastline. The teaching about the mystical mountain and mythical water have been passed throughout generations and probably become a chief reason for them to respectfully hold their tradition in respecting both the areas. This concept is called Nyegara Gunung. It stands on the truth that the mountain and the sea are part of mother nature that gives tremendous impact on life. Many customs around the globe also share the concept of the sacred mountain as well as a myth about the sea. The folk views environment conservation becomes the primary key to live in harmony. Therefore they stand for anything in regards to keep the nature undisturbed. Through ritual, they express their gratitude to the supreme being as well as to teach their offspring to respect what they have on the island.